Liver damage during organ donor procurement in donation after circulatory death compared with donation after brain death. Issue 3 (20th December 2012) - Ausania, F.; White, S. A.; Coates, R.; Hulme, W.; Manas, D. M.
Abstract Background: During the past decade the number of livers recovered and transplanted from donation after circulatory death (DCD) donors has increased significantly. As reported previously, injuries are more frequent during kidney procurement from DCD than from donation after brain death (DBD) donors. This aim of this study was to compare outcomes between DCD and DBD with respect to liver injuries. Methods: Data on liver injuries in organs procured between 2000 and 2010 were obtained from the UK Transplant Registry. Results: A total of 7146 livers were recovered from deceased donors during the study, 628 (8·8 per cent) from DCD donors. Injuries occurred in 1001 procedures (14·0 per cent). There were more arterial (1·6 versus 1·0 per cent), portal (0·5 versus 0·3 per cent) and caval (0·3 versus 0·2 per cent) injuries in the DBD group than in the DCD group, although none of these findings was statistically significant. Capsular injuries occurred more frequently in DCD than DBD (15·6 versus 11·4 per cent; P = 0·002). There was no significant difference between DCD and DBD groups in liver discard rates related to damage. Conclusion: There were no differences in terms of vascular injuries between DCD and DBD livers, although capsular injuries occurred more frequently in DCD organs. Continuing the trend for increased frequency of DCD liver recovery, and ensuring that there is an adequately skilled surgical team available for procurement, is vital to improving the utilization of DCD livers. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd.